2017
DOI: 10.7150/ijbs.18331
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epigenetics in Uveal Melanoma

Abstract: Uveal melanoma (UM) is a severe human malignancy with a high mortality rate that demands continued research into new and alternative forms of prevention and treatment. The emerging field of epigenetics is beginning to unfold an era of contemporary approaches to reducing the risk and improving the clinical treatment of UM. Epigenetic changes have a high prevalence rate in cancer, are reversible in nature, and can lead to cancer characteristics even in mutation-free cells. The information contained in this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 78 publications
1
28
0
1
Order By: Relevance
“…It has been reported that 1 in 8 women in her life might suffer from BC in America 2 . Recent studies have focused on identifying epigenetic signatures that are associated with tumor progression and patient prognosis to improve therapy and recovery 3 - 5 . Although some tumor suppressors and oncogenes have been identified to play central roles in tumorigenesis and development of BC 6 - 8 , the exact molecular mechanisms have not been totally elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 1 in 8 women in her life might suffer from BC in America 2 . Recent studies have focused on identifying epigenetic signatures that are associated with tumor progression and patient prognosis to improve therapy and recovery 3 - 5 . Although some tumor suppressors and oncogenes have been identified to play central roles in tumorigenesis and development of BC 6 - 8 , the exact molecular mechanisms have not been totally elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 One of the new developments in the management of uveal melanoma is the use of microRNA molecules that play a role in gene silencing or posttranscriptional regulation of genes involved in development of uveal melanomas. 35,36 MicroRNA-34a was found to be a proapoptotic transcriptional target of the p53 tumor suppressor gene effector network. 37 MicroRNA-34a has been shown to downregulate c-Met levels, another pro-oncogenic pathway to tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Decitabine is a Food and Drug Administration (FDA)-approved drug for treatment of haematological malignancies, and while 3-Deazaneplanocin A is not currently FDA approved, it has been investigated for its role in inhibiting histone methylation in acute myeloid leukaemia and are therefore examples of drug repurposing opportunities for non-cancerous rare ophthalmic disease. Although retinoblastoma and uveal/intraocular melanoma are not included in this review, epigenetics and rare tumorous ophthalmic conditions have been reviewed extensively elsewhere within the last 2 years, with extensive studies illustrating the association of hypermethylation of tumour suppressor gene promoter regions and ophthalmic tumorigenesis 56 57. Therefore, the association of methylation with ophthalmic disease, coupled with attenuated retinal degeneration following methyltransferase inhibition in the two cited articles,41 53 highlights the need to conduct further investigations into epigenetic inhibitors as therapeutic agents for both tumorous and non-tumorous ophthalmic disease.…”
Section: Discussionmentioning
confidence: 99%